Liar & spy - Stead, Rebecca (New York : Wendy Lamb Books, 2012)
Seventh-grader Georges adjusts to moving from a house to an apartment, his father's efforts to start a new business, his mother's extra shifts as a nurse, being picked on at school, and Safer, a boy who wants his help spying on another resident of their building.
Keywords: Spy stories; Apartment houses -- Juvenile fiction; Families -- New York (State) -- New York -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Brooklyn (New York, N.Y.) -- Juvenile fiction